EFEKTIVITAS MEDIA SOSIAL INSTAGRAM @LOKER_KOTASURABAYA DALAM PEMENUHAN KEBUTUHAN INFORMASI LOWONGAN PEKERJAAN DI SURABAYA - Erfianah, Milani Eka; Huda, Anam Miftakhul (The Commercium, 2022)
This research is entitled "Effectiveness of Instagram @loker_kotasurabaya Social Media in Fulfilling JobVacancies Information Needs in Surabaya". A study of the effectiveness of social media using Uses and GratificationTheory which is also to find out the gap between the amount of desire sought and the reality obtained. The theory thatis considered relevant in this research is Uses and Gratification, where media users have an active right to choosewhat media is able to meet their needs. Determination of the sample using a random sampling technique from thepopulation of followers of the Instagram account @loker_kotasurabaya. Data was collected using a survey method,namely by distributing questionnaires. While the data analysis was carried out through gap analysis, analysis of TCRvalues, hypothesis testing by calculating t-count and t-table which resulted in Ho being rejected, Ha accepted.Because, t-count = 0.04243 is smaller than t-table = 0.1166. And from the results of the TCR analysis, the Instagramaccount @loker_kotasurabaya is very effective in meeting the information needs of followers. The research indicatorsare Information with Accurate, Timely, Relevant, Complete markers measured in the Gratification Sought andGratification Obtained Dimensions indicating the Very Effective category. With a percentage of the TCR GratificationSought Value / Desire Wanted with a percentage of 92%. Meanwhile, at the Gratification Obtained level, theInformation indicator gets a percentage of 87%.Keywords : Instagram Effectiveness, Uses and Gratification Theory, Gaps